The Inner Conflict of the Main Character in the Novel "Tersesat Setelah Terbaru Berlahir" by Yoga Zen: A Study of Literary Psychology: Konflik Batin Tokoh Utama dalam Novel Tersesat Setelah Terlahir Kembali Karya Yoga Zen: Kajian Psikologi Sastra - Azzahra, Sakinah; Marwiah; K, Abdul Munir (Indonesian Journal of Innovation Studies, 2025)
Background: Literary works often portray complex psychological conditions through characters’ inner struggles, providing insight into human emotional dynamics. Specific background: The novel Tersesat Setelah Terlahir Kembali presents a protagonist who experiences profound psychological turmoil following traumatic loss. Knowledge gap: Previous literary studies in Indonesia frequently describe inner conflict superficially and rarely integrate psychoanalytic and humanistic psychological frameworks in a structured manner. Aims: This study aims to examine the stages of the protagonist’s inner conflict and psychological disturbance using Sigmund Freud’s psychoanalytic concepts and Abraham Maslow’s hierarchy of needs. Results: The findings reveal three sequential phases of inner conflict: initial emotional pressure, psychological breakdown, and posttraumatic emotional confusion, marked by imbalance among id, ego, and superego alongside unmet psychological needs. Novelty: This study offers an integrated reading of Freudian and Maslovian perspectives to explain the gradual progression of literary inner conflict. Implications: The results contribute to literary psychology by demonstrating how fictional narratives reflect complex human psychological processes and provide a deeper understanding of trauma representation in literature. Highlights The protagonist’s inner conflict unfolds through three psychological stages. Trauma is portrayed as a gradual and cumulative psychological process. Freudian and Maslovian perspectives offer a complementary literary reading. Keywords Literary Psychology, Inner Conflict, Psychological Trauma, Psychoanalytic Theory, Humanistic Psychology